2014
DOI: 10.1186/1472-6874-14-127
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence and physical and mental health among women utilizing community health services in Gujarat, India

Abstract: BackgroundIntimate partner violence (IPV) is a significant public health threat which causes injury and acute and chronic physical and mental health problems. In India, a high percentage of women experience IPV. The purposes of this study include 1) to describe the lifetime prevalence of IPV, and 2) to examine the association between IPV and physical and mental health well-being, among women utilizing community health services for the economically disadvantaged in India.MethodsWomen utilizing community health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 54 publications
2
33
0
Order By: Relevance
“…Those who experience sexual assault may also fear of not being believed (Sable, Danis, Mauzy, & Gallagher, 2006). Non-help seeking for intimate partner violence (IPV) is a problem in Japan and India (Kamimura, Bybee, & Yoshihama, 2014;Kamimura, Ganta, Myers, & Thomas, 2014;Kamimura, Yoshihama, & Bybee, 2013), while the information about sexual violence and help seeking is limited in these countries. This study suggests that rape myth acceptance may be one of the reasons behind non-help seeking in these countries.…”
Section: Discussionmentioning
confidence: 99%
“…Those who experience sexual assault may also fear of not being believed (Sable, Danis, Mauzy, & Gallagher, 2006). Non-help seeking for intimate partner violence (IPV) is a problem in Japan and India (Kamimura, Bybee, & Yoshihama, 2014;Kamimura, Ganta, Myers, & Thomas, 2014;Kamimura, Yoshihama, & Bybee, 2013), while the information about sexual violence and help seeking is limited in these countries. This study suggests that rape myth acceptance may be one of the reasons behind non-help seeking in these countries.…”
Section: Discussionmentioning
confidence: 99%
“…3 While high intent was seen in the arranged group than the love group in our study, Sarkar et al found in his study on attempters and selfharmers, in the former, the acts were thoughtful, intent and fatality was high, with less voluntary disclosure; the latter were emotionally unstable with personality difficulties, with impulsive, low intent and less lethal attempts, and most seeking rescue eventually. 55,56 In the studies by Pearson & Liu, 26 and Kamimura et al, 27 couple satisfaction rates were still good in 40% spouses. Similarly, in this study too, couple satisfaction moderated suicidal intent in arranged marriage, but only mildly in love marriage.…”
Section: Discussionmentioning
confidence: 96%
“…25 In a study of suicide attempts, 40% were young rural females under 35 years of age, 40% had debts and 40% had battering as the triggering stressful events. 26,27 Protective Factors vs. Attrition of Love Dyadic adjustment and couple satisfaction 28,29 diminishes the intensity of interpersonal conflicts.…”
Section: Precipitating Factorsmentioning
confidence: 99%
“…The methods of the entire project have been presented elsewhere (Kamimura, Ganta, Myers, & Thomas, 2014). The staff of the community organization and the research team worked together to develop the survey instrument, study protocol, participant recruitment strategies, and interpreting study results.…”
Section: Overviewmentioning
confidence: 99%